2019
DOI: 10.21273/hortsci13510-18
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Inflorescence Dry Weight and Cannabinoid Content in Medical Cannabis Using Controlled Drought Stress

Abstract: Additional index words. Cannabis sativa, marijuana, deficit irrigation, plant water potential, medicinal crops, volumetric soil moisture content Abstract. Controlled application of drought can increase secondary metabolite concentrations in some essential oil-producing crops. To evaluate the effects of drought on cannabis (Cannabis sativa L.) inflorescence dry weight and cannabinoid content, drought stress was applied to container-grown cannabis plants through gradual growing substrate drying under controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 52 publications
1
61
1
1
Order By: Relevance
“…This finding is important for C. sativa cultivators to consider, given many cultivators are interested in increasing cannabinoid concentrations through controlled stress applications to improve the highly economically and medically valuable inflorescence. It has been shown that cannabinoid concentrations can be increased through controlled drought stress application (Caplan et al, 2019). Caplan et al (2019) increased THCA and CBDA concentrations by 12 and 13%, respectively, compared to the control, by applying a drought stress that induced a 50% decrease in leaf angle from the turgid state at 39 DFS and then allowing the plant to recover.…”
Section: Nacl Decreases Yield and Potencymentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is important for C. sativa cultivators to consider, given many cultivators are interested in increasing cannabinoid concentrations through controlled stress applications to improve the highly economically and medically valuable inflorescence. It has been shown that cannabinoid concentrations can be increased through controlled drought stress application (Caplan et al, 2019). Caplan et al (2019) increased THCA and CBDA concentrations by 12 and 13%, respectively, compared to the control, by applying a drought stress that induced a 50% decrease in leaf angle from the turgid state at 39 DFS and then allowing the plant to recover.…”
Section: Nacl Decreases Yield and Potencymentioning
confidence: 99%
“…It has been shown that cannabinoid concentrations can be increased through controlled drought stress application (Caplan et al, 2019). Caplan et al (2019) increased THCA and CBDA concentrations by 12 and 13%, respectively, compared to the control, by applying a drought stress that induced a 50% decrease in leaf angle from the turgid state at 39 DFS and then allowing the plant to recover. Given that drought and salt can induce stress on plants through similar functions (Munns, 2002), the opposing results between our study and Caplan et al (2019) is likely a result of stress being applied in a cumulative or perpetual fashion versus a periodic or single occurrence.…”
Section: Nacl Decreases Yield and Potencymentioning
confidence: 99%
See 1 more Smart Citation
“…Delta‐9‐tetrahydrocannabinol is one of the cannabinoids synthesized in hemp . The cannabinoids are known as secondary metabolites synthesized in leaves and inflorescence to prevent plant from abiotic stress such as drought and ultraviolet radiation . Hemp sprouts, which did not have leaves and inflorescence, were produced with a continuous water‐change type mini‐sprouter under dark conditions in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cannabinoids, THC and CBD were most discussed for having their antioxidant properties 90 . Earlier increasing of THC, THCA, CBD, and CBDA were predicted as stress indicators along with some other secondary metabolites in hemp plant under controlled drought stress 89 . It was also reported that THCA induces necrotic cell death in Cannabis cells and leaves 91 .…”
Section: Effect Of Led Spectra On Antioxidant Activitiesmentioning
confidence: 96%